Reviewing Bilingual Education Program - Tjalla, Magdahalena (Al-Lisan, 2015)
This paper is aimed at revealing the benefits of bilingual program in which English and the native language of the students are thought to learn subjects in classrooms. Through this paper, the writer studied the phenomena of bilingual education all over the world which is rooted in American history and then compared it with bilingual program in Indonesian schools, through the study of some references written on bilngual education and bilngual program.  This study showed that bilingual program in the United State of America was done to maintain and protect  cultural diversity of a great immigrant in America who spoke  English as the second language.   This study also showed that bilingual program in Asia is considered crucial by the government to make their people able to compete in international scope in field of business, education, politics, and tourism. In Indonesian schools, bilingual program is in form of teaching several subjects such as science and mathematics in English and the other subjects is taught in Indonesian. The final goal of bilingual program in Indonesia is to raise the standard of educational system. To achieve the goal,  government tried to set up some model schools and supported the other schools to become model schools.